Dynamics of self-compressed argon and helium plasma streams in the MPC facility. (16th June 2016) - Ladygina, M S; Marchenko, A K; Solyakov, D G; Petrov, Yu V; Makhlaj, V A; Yeliseyev, D V; Garkusha, I E; Cherednichenko, T N
Abstract: The results of experimental investigations on self-compressed plasma streams and compression zone formation are presented for varied mass flow rate and initial concentrations of particles of working gas that depend on initial pressure. Experiments were carried out in the Magnetoplasma Compressor (MPC) facility. Space–time distributions of the electric current and electron density in the plasma stream compression region were measured under different experimental conditions. High-speed images of plasma stream dynamics in the MPC accelerating channel with a high temporal resolution were also obtained for different initial pressures. The experimental results show a strong dependence of plasma stream parameters and compression zone location on the initial gas concentration. The maximum electron density is obtained in the range of Ne = (1 ÷ 5) × 10 18 cm −3 . Plasma streams have a good radial symmetry under all experimental conditions. The distributions of plasma parameters along the plasma stream flows are discussed.